(untitled) (Annals of Medical Research, 2021)
Aim: Nursing is an applied profession and it contains some basic concepts. These concepts are health, disease, human, environment, nursing. In addition to these concepts, the concept of care is a compulsory concept. Concepts can change meaning according to place, time and even user. Metaphors contribute to the analysis of how concepts are perceived. The essence of the metaphor is to understand and experience something according to another kind of thing. This study aims to reveal nursing students’ perceptions related to basic principles about nursing by means of metaphors and evaluate these metaphors according to common goal and features. Material and Methods: This study has been carried out with 74 people who are the first year nursing students and agreed to participate in the study. While collecting research data, a participant information form which was developed by researchers and composed of 15 questions including multiple choice and open-ended ones has been used. Participant information form; İt consisted of sociodemographic questions and open-ended questions (used in determining the metaphors of nursing basic concepts (health, disease, human, environment, nursing, care). For example; “Health is like ...” “Because ...”Results: In our study, 182 metaphors have been developed by taking into consideration what the participants have said about these concepts. 76 (41.7%) of these metaphors are positive, 68 of them (37.3%) are negative and 38 (20.8%) of them is both positive and negative. Conclusions: Nursing students mostly perceive nursing profession, care and health positively.Keywords: Nursing; student; concept; metaphor.